RESPON PAKISTAN TERHADAP PENCABUTAN STATUS OTONOMI KHUSUS KASHMIR OLEH INDIA TAHUN 2019 - Yudistira, Dwiki; Pasan, Etha; Wahyu, Frentika (Department of International Relations, Universitas Mulawarman, 2022)
In 1948 India decided to give Kashmir special autonomy status which was written in Article 370 and 35A India Constitution. In August 2019. India decided to revoke the special autonomy status of Kashmir due to frequent conflicts in the Kashmir region that the local Kashmiri official could not resolve This policy made several countries and International Organizations respond to the policies issued by India. Pakistan is the only state actor who has responded to the actions taken by India which in increasing the escalation of the conflict and making relations between the two countries worse. The result of this research is the response issued by Pakistan, there are four. The first, Submission of a letter by Pakistan to the National Security Council (UNSC), second is the suspension of trade relations, third is the suspension of rail service and fourthly the decline in diplomatic relations.